User Interface/User Experience Design for Mobile-Based Project Management Application Using Design Thinking Approach - A H Makalalag; Y A Ekawardhani; Theresia Valentina Lumban Gaol (International Journal of Education, Information Technology, and Others, 2021)
This study aims to design a mobile-based project management application design. User Interface/User Experience has become an important part of doing activities in digital media. Including facilitating study activities or certain jobs. This research is a User Interface/User Experience design for an information system that helps users manage projects and tasks. This application's design refers to the design thinking method to gain user experience, especially those with high mobility. Furthermore, in User Experience, a flat design is used, so it is easy to capture and use. Design thinking provides search directions about user needs, and flat design complements the ease of user experience. This research aims to create a User Interface/User Experience design that is user-friendly and attractive. This study concludes that users are helped by the application and have benefits for managing projects and tasks.